High-resolution Land Cover Change from Low-resolution Labels: Simple Baselines for the 2021 IEEE GRSS Data Fusion Contest - Malkin, Nikolay; Robinson, Caleb; Jojic, Nebojsa (2021)
We present simple algorithms for land cover change detection in the 2021 IEEE GRSS Data Fusion Contest. The task of the contest is to create high-resolution (1m / pixel) land cover change maps of a study area in Maryland, USA, given multi-resolution imagery and label data. We study several baseline models for this task and discuss directions for further research. See this https URL for the data and this https URL for an implementation of these baselines.